Impact of Hearing Loss in the Pediatric Population on Physical Activity and Daily Life: A Literature Review - Florek, Jakub; Dziuba, Natalia; Damek, Magdalena; Dyjak, Natalia; Grzyb, Michał; Dziuba, Miłosz (Quality in Sport, 2026)
Background: Hearing loss is a common sensory impairment in the pediatric population that can significantly affect speech, language development, academic performance, and social interaction. Beyond communication challenges, it may also influence physical activity. Aim: The aim of this literature review is to critically evaluate the evidence on how hearing loss affects physical activity participation and daily functioning in children. Methodology: A literature search was conducted to identify relevant studies published between 1992 and 2026 using electronic databases, including PubMed, Google Scholar, ResearchGate, Scopus and Web of Science. Results: Children with hearing loss often engage less in physical activity and may face balance, coordination, and motor skill challenges. Hearing loss can also affect daily life and social participation, although early intervention and appropriate support can help improve functional outcomes and quality of life. Conclusions: Young people with hearing loss are generally less physically active and participate less in sports than their hearing peers due to communication, environmental, and psychosocial barriers. Since physical activity supports both physical and mental well-being, adapting sports programs to their needs can improve participation and overall psychosocial functioning.